Analysis of relaxation of local government budgeting on the achievement of the Bengkulu City government’s key performance indicators during the covid-19 period - Suryani, Pesi; Gaol, Lasando Lumban; Daurrohmah, Eka Wirajuang (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2023)
This study explores the impact of relaxation on the Bengkulu City local government budget during the Covid-19 period on key performance indicators. This study used a qualitative approach with documentary methods and interviews at the Regional Financial and Asset Management Agency and the Health Office involving Budget Users, PPTK, Treasurer, and financial management staff as informants. The data analysis used is a content analysis using the Nvivo software. There are two findings in this research, the first is that budget reallocation during the pandemic can affect the achievement of the Main Performance Indicators of Regional Apparatus Organizations which have indicators of financial ratios, such as the Regional Finance and Asset Management Agency. Financial indicators, such as financial ratios and PAD, have declined due to the weakening economy, decreased tax revenue during the pandemic, and budget reallocations. However, the budget reallocation during the pandemic was not directly affected by the Main Performance Indicators of Regional Apparatus Organizations that do not use financial indicators such as the Health Service. Where the two KPI indicators of the Bengkulu City Health Service were all achieved according to the targets set. The implications of this research are as input to the Bengkulu City Government related to refocusing and reallocating the budget so that it can still achieve the main performance indicators.